Revision of the funnel-web spider genus Novalena (Araneae: Agelenidae) - Maya-Morales, Julieta; Jiménez, María Luisa (Zootaxa, 2017)
The Western Hemisphere genus Novalena Chamberlin & Ivie 1942 (Araneae: Agelenidae) is revised. The genus now includes a total of 53 species, of which 40 are new species from USA, Mexico, Guatemala, and Costa Rica: N. ajusco sp. nov. (♀), N. alamo sp. nov. (♂), N. alvarezi sp. nov. (♀), N. atzimbo sp. nov. (♀), N. bosencheve sp. nov. (♂), N. chamberlini sp. nov. (♂ ♀), N. cieneguilla sp. nov. (♀), N. cintalapa sp. nov. (♂ ♀), N. clara sp. nov. (♂ ♀), N. comaltepec sp. nov. (♀), N. creel sp. nov. (♂ ♀), N. dentata sp. nov. (♂ ♀), N. divisadero sp. nov. (♀), N. durango sp. nov. (♀), N. franckei sp. nov. (♂ ♀), N. garnica sp. nov. (♂ ♀), N. gibarrai sp. nov. (♂ ♀), N. irazu sp. nov. (♀), N. iviei sp. nov. (♂), N. ixtlan sp. nov. (♂), N. jiquilpan sp. nov. (♀), N. leonensis sp. nov. (♂ ♀), N. mexiquensis sp. nov. (♂ ♀), N. oaxaca sp. nov. (♂ ♀), N. paricutin sp. nov. (♀), N. perote sp. nov. (♂ ♀), N. plata sp. nov. (♀), N. poncei sp. nov. (♂ ♀), N. popoca sp. nov. (♀), N. prieta sp. nov. (♀), N. puebla sp. nov. (♂ ♀), N. punta sp. nov. (♂ ♀), N. rothi sp. nov. (♂ ♀), N. saltoensis sp. nov. (♀), N. sinaloa sp. nov. (♀), N. tacana sp. nov. (♂ ♀), N. triunfo sp. nov. (♀), N. valdezi sp. nov. (♂ ♀), N. victoria sp. nov. (♀), and N. volcanes sp. nov. (♀). Nine are previously described species: N. annamae (Gertsch & Davis 1940), N. attenuata (F.O. Pickard-Cambridge 1902), N. bipartita (Kraus 1955), N. calavera Chamberlin & Ivie 1942, N. costata (F.O. Pickard-Cambridge 1902), N. laticava (Kraus 1955), N. orizaba (Banks 1898), N. shlomitae (García-Villafuerte 2009), and N. simplex (F.O. Pickard-Cambridge 1902). Four new synonyms are proposed: N. pina Chamberlin & Ivie 1942 = N. intermedia (Chamberlin & Gertsch 1930); N. idahoana (Gertsch 1934) and N. wawona Chamberlin & Ivie 1942 = N. lutzi (Gertsch 1933); N. tolucana (Gertsch & Davis 1940) = N. approximata (Gertsch & Ivie 1936). One species is transferred from Melpomene back to Novalena: N. bipunctata Roth 1967 stat. rev. One species is transferred to Hoffmannilena Maya-Morales & Jiménez 2016: H. nova (O. Pickard-Cambridge 1896) comb. nov.